1966
DOI: 10.1002/app.1966.070101208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight distribution in alkyd resins. Part III. Presence of microgel in alkyd resins

Abstract: SynopsisAlkyd resins which have the same overall chemical composition and the same degree of polymerization have been prepared from synthetic mixtures of mono-, di-, and triglycendm of linoleic acid, glycerol, and phthalic anhydride. The properties of these resins difiered significantly. Microgel particles are present in all resins, but the quantity and size of the gel particles is a function of the glyceride composition. The concept of microgel is used to explain the solution and film forming properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The 10 μm × 10 μm scan shows the larger nodules range upwards of 100 nm in height and more than 2 μm in width. Though post‐curing of the epoxy normally results in increased mechanical properties as additional cross‐linking occurs, 52,67,68 several authors have reported nodular structures do not change with post‐cures even above the glass transition temperature T g 34,35,69,70,71 . Though the reason for this is not fully understood, it appears nodular formation occurs at random locations on the surface before gelation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10 μm × 10 μm scan shows the larger nodules range upwards of 100 nm in height and more than 2 μm in width. Though post‐curing of the epoxy normally results in increased mechanical properties as additional cross‐linking occurs, 52,67,68 several authors have reported nodular structures do not change with post‐cures even above the glass transition temperature T g 34,35,69,70,71 . Though the reason for this is not fully understood, it appears nodular formation occurs at random locations on the surface before gelation.…”
Section: Resultsmentioning
confidence: 99%
“…Though post-curing of the epoxy normally results in increased mechanical properties as additional cross-linking occurs, 52,67,68 several authors have reported nodular structures do not change with post-cures even above the glass transition temperature T g . 34,35,69,70,71 Though the reason for this is not fully understood, it appears nodular formation occurs at random locations on the surface before gelation. Though the exact reason is unknown, the air pockets generated during high shearing, which are not completely removed may play a role, as these pockets possibly contain higher moisture and CO 2 content than the bulk.…”
Section: Provide a Visualization Tomentioning
confidence: 99%
“…Microgels have also been detected as a component of alkyd resins, an early but still important binder of organic coatings [316][317][318][319][320][321] and are accountable for their ability to fill pores, fissures and other irregularities of the substrate such as wood. This property may be explained by the size of the microgels which pre vents the paint becoming soaked up by the substrate.…”
Section: Applications Of Microgelsmentioning
confidence: 99%
“…and draws attention to the parallel between the cure and the polyesterification reactions of alkyd resins. Solomon et al 206 have invoked the formation of microgel particles formed from micelles at whose surface rapid polyesterification occurs.…”
Section: Diacid Anhydridesmentioning
confidence: 99%